2019
DOI: 10.1016/j.neuron.2019.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Functional Role of NaV1.7 in Human Nociception

Abstract: SummaryLoss-of-function mutations in NaV1.7 cause congenital insensitivity to pain (CIP); this voltage-gated sodium channel is therefore a key target for analgesic drug development. Utilizing a multi-modal approach, we investigated how NaV1.7 mutations lead to human pain insensitivity. Skin biopsy and microneurography revealed an absence of C-fiber nociceptors in CIP patients, reflected in a reduced cortical response to capsaicin on fMRI. Epitope tagging of endogenous NaV1.7 revealed the channel to be localize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
177
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(197 citation statements)
references
References 85 publications
(159 reference statements)
10
177
0
Order By: Relevance
“…We confirmed the localisation of PACAP within sensory afferents in human skin using immunohistochemistry ( Fig 4A). Human induced pluripotent stem cell-derived (hiPSCd) sensory neurons have been shown to replicate many of the molecular, morphological and functional features of native human sensory neurons 12,13,14 and so we used these to study the functional effects of PACAP. These hiPSCd-sensory neurons demonstrated strong mRNA expression of both ADCYAP1, as well as its high affinity receptor PAC1 ( Fig 4B).…”
Section: Pacap Is Expressed In Human Skin and Facilitates Neurite Outmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed the localisation of PACAP within sensory afferents in human skin using immunohistochemistry ( Fig 4A). Human induced pluripotent stem cell-derived (hiPSCd) sensory neurons have been shown to replicate many of the molecular, morphological and functional features of native human sensory neurons 12,13,14 and so we used these to study the functional effects of PACAP. These hiPSCd-sensory neurons demonstrated strong mRNA expression of both ADCYAP1, as well as its high affinity receptor PAC1 ( Fig 4B).…”
Section: Pacap Is Expressed In Human Skin and Facilitates Neurite Outmentioning
confidence: 99%
“…In order to determine a potential regenerative role of PACAP in human primary sensory neurons, we dissociated mature hiPSCd-sensory neurons and assessed their ability to regenerate neurites, as we have previously described 14 . Neurons were enzymatically treated for 30 min with 0.1% Trypsin (ThermoFisher), followed by mechanical dissociation with a fire polished glass pipette.…”
Section: Human Sensory Neuron Regeneration Modelmentioning
confidence: 99%
“…8 It has been assumed that NaV1.7 plays a key role in action potential initiation in the peripheral nerve endings of nociceptors, but neurogenic inflammation dependent on action potential propagation is not compromised in mouse or human NaV1.7 nulls. [9][10][11] Loss of NaV1.7 also leads to enhanced endogenous opioid signalling and opioid receptor function in sensory neurons, and the opioid antagonist naloxone substantially reverses analgesia associated with channel deletion. [12][13][14] Conditional knockout of Scn9a in the peripheral sensory neurons of mice reproduces the pain insensitivity of NaV1.7 null humans, affirming the nociceptor as the locus of analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the crucial role of NaV1.7 in pain sensing discovered in part from patients who do not experience pain (congenital insensitivity to pain, CIP); selective block of NaV1.7 currents failed to significantly abolish firing of C fibres. Furthermore, iPSC nociceptors humanized from patients with CIP are capable of firing action potentials suggesting that NaV1.7 is not critical for firing (162). NaV1.7 channels which are also TTX-S and have kinetic properties more comparable to NaV1.6, were found to play a minimal role in C fibres activation (305).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same study found NaV1.7 current crucial for defining the threshold of activation of action potentials in iPSC derived nociceptors (161). Concurrently, recording from iPSC nociceptors derived from CIP patients (NaV1.7 loss-of-function) were less responsive to slow ramp depolarisations than WT iPSC derived nociceptors (162).…”
Section: Dorsal Root Ganglionmentioning
confidence: 98%